Assessment of Poa annua resistance to clethodim in Costa Rica. - Rodríguez-Ruiz, Ana María (2015)
The objective of this study was to check for the presence of resistance to clethodim in Poa annua populations observed in onion fields in the highlands of Cartago, Costa Rica. Two experiments were conducted; the first one was carried out, in 2007, in a greenhouse at the Fabio Baudrit Moreno Agricultural Experiment Station (EEAFBM, in Spanish), with seeds of plants from a farm where clethodim exercised good control (S population), and from another farm where clethodim showed a deficient control (R population). Both S and R populations were treated with different doses of clethodim (0.5X, 1.0X, 1.5X and 2.0X), being X the recommended commercial dose). In this experiment, control of the R population was 44% and 17% at doses of 1.5X and 2.0X, respectively, whereas control of the S population was 100% at either of those doses. The second experiment was carried out in 2009, seeds of two other P. annua populations were collected in a similar way: one population from an area where weed control was satisfactory (S), and the other population from an area of the farm where control was deficient (R). Seeds were sown, depending on the type, in plastic pots and sprayed with clethodim at doses of: 0. 1X, 2X, 4X, 8X, and 16X. There were significant differences in the reactions to clethodim of both P. annua populations The S population showed a higher percentage of control and less surviving plants than the R population. Several plants of the R population resisted up to 16X commercial doses of clethodim. Results of both experiments suggest the presence of P. annua populations resistant to clethodim.